PENGARUH INFLASI, SUKU BUNGA DAN NPF TERHADAP PENDAPATAN BANK SYARIAH DI INDONIESIA - Siti Zainab Siregar (ITB AAS INDONESIA Surakarta, 2022)
One of the factors supporting monetary policy in order to be done effectively is the existence of banking institutions. The development and progress of banking institutions is reflected in the type of services through their products and features, the expansion of banking networks, the increasing quality of banks in the mobility of public funds by providing loans to productive sectors, and bank management is increasingly efficient and dynamic. With these advances, the Islamic banking system and conventional banking together synergistically support the mobilization of public funds more broadly to improve financing capabilities for sectors of the national economy. This study aims to look at the simultaneous influence of Inflation, Interest Rates and NPF on Islamic Bank Income in Indonesia. The type of This research is quantitative study with a sample number of 36 data on the monthly report of Inflation, Interest Rates (SBI), NPF, and Sharia Bank Income from 2017-2019. The results in this study obtained that Inflation did not have a positive and significant effect on Islamic Bank Income with T count -1,292 < T table 2,037, Interest Rates also did not have a positive and significant effect on Islamic Bank Income with T count -3,959 < T table 2,037, and NPF did not have a positive and significant effect on Sharia Bank Income with T count -8,664 < T table 2,037. Then simultaneously Inflation, Interest Rates and NPF to Islamic Bank Income with F count 45,304 > F table 2.901 with a value of R Squared of 0.809 or by 80.9% explained by variables inflation, interest rates and NPF and the remaining 19.1% influenced by other variables outside of this study. Keywords: Inflation, Interest Rates, NPF, Islamic Bank Revenue